Role of Continuous Low Pressure Suction in Management of Traumatic Haemothorax and/or Haemopneumothorax: Experiences at NIDCH and CMH Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The number of chest trauma patients has rapidly increased in this 21st century of high speed travel, violence, natural and manmade disasters. Most of the patients present with haemothorax and/or haemopneumothorax. Drainage of haemothorax and/or haemopnumothorax by tube thoracostomy is the main stay of treatment. Even timely insertion of chest tube sometimes fails to drain haemothorax adequately and results in clotted haemothorax for which surgical management is needed. Application of continuous low pressure suction through chest tube hastens evacuation of blood and reduces incidence of clotted haemothorax and thoracotomy.Objective: The aim of this study is to find out the effectiveness of continuous low pressure suction in evacuation of blood and air from pleural cavity, in early re-expansion of lung and reduction of clotted haemothorax in comparison with simple chest tube drainage.Methods: This randomized controlled clinical trial was conducted at Combined Military Hospital (CMH) Dhaka and National Institute of Diseases of the Chest and Hospital (NIDCH), Mohakali, Dhaka from April 2012 to March 2013. A total of 60 patients with blunt and penetrating chest trauma fulfilling the selection criteria enrolled in this study. Patients were allocated into two groups. Patients who received continuous low pressure suction on their chest tubes were leveled as group-I and patients who received only chest tube drainage were leveled as group-II. Data were collected by interview, observation, clinical examination and investigation results. Data were processed and analyzed by using statistical test.Results: The mean chest tube duration was 7.13±2.1 days with a range from 5-16 days in group-I as compared to 11.83±5.26 days with a range from 6-28 days in group-II. The mean duration of hospital stay was 8.97±2.28 days with a range from 6-18 days in group-I as opposed to 13.47±5.53 days with a range from 8-32 days in group-II. In group-I 96.7% patients achieved full lung re-expansion while 3.3% patients had clotted haemothorax for which they underwent thoracotomy and evacuation of clot. In group-II who was on simple chest tube drainage, 76.7% patients achieved full lung re-expansion and 23.3% patient had clotted haemothorax and required thoracotomy.Conclusion: Continuous low pressure suction is a useful device in the management of traumatic haemothorax and/or haemopneumothorax. It reduces morbidity, hospital stay and cost of thoracic surgery.Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014